2018
DOI: 10.3892/br.2018.1092
|View full text |Cite
|
Sign up to set email alerts
|

Urinary diagnostic proteomic markers for dynapenia in cancer patients

Abstract: Abstract. Dynapenia is defined as the age-related loss of muscle strength, and plays a significant role in the loss of physical function and increased risk of disability among older individuals. The need for an early diagnosis supports the search for a biomarker that reflects muscle 'weakening'. This has previously proven difficult due to patient heterogeneity at presentation and lack of understanding of the underlying molecular mechanisms. The aim of the present study was to identify potential urinary biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…This study identified dynapenia in 23.4% of the evaluated patients, who were mostly malnourished and had gastrointestinal tract cancer. Similar studies carried out in both adults and the elderly showed that dynapenia was present in 24.4% [36] and 44.9% [37] of cancer patients, respectively, while yet another study reported that 30.9% of the elderly population under evaluation presented dynapenia [13].…”
Section: Discussionmentioning
confidence: 77%
“…This study identified dynapenia in 23.4% of the evaluated patients, who were mostly malnourished and had gastrointestinal tract cancer. Similar studies carried out in both adults and the elderly showed that dynapenia was present in 24.4% [36] and 44.9% [37] of cancer patients, respectively, while yet another study reported that 30.9% of the elderly population under evaluation presented dynapenia [13].…”
Section: Discussionmentioning
confidence: 77%
“…Another mass spectrometry-based technique employed to identify potential urinary biomarkers is surface-enhanced laser desorption/ionization; together with model building using decision tree analysis, Husi et al identified prospective biomarkers of myosteatosis [ 44 ] and dynapenia (the age-associated loss of muscle strength) [ 42 ] by comparing the expression profiles of potential biomarker peaks between groups, to establish a proteomic fingerprint pattern which, upon validation, can be used in clinical diagnostics. Such an approach not only allows stratification and pattern matching to search for specific cachexia-related biomarkers in the urine of cancer patients, but also identifies key protein fragments that may be related to the pathophysiology of muscle wasting in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach not only allows stratification and pattern matching to search for specific cachexia-related biomarkers in the urine of cancer patients, but also identifies key protein fragments that may be related to the pathophysiology of muscle wasting in cancer. For example, the downregulation of fragments of CTSC, agrin, ARSA and GFAP was observed in patients with upper gastrointestinal tract cancer and myosteatotic vs. non-myosteatotic [ 44 ], whilst downregulation of annexin A1 and COL15A1 chain was observed in patients with a mixture of cancers and with leg-power measurement-based dynapenia [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ease and non-invasive nature by which urine can be obtained makes it an appealing source for potential biomarkers. Previous investigation has highlighted promising target markers in patients with gastrointestinal cancers [25,26] and even links to decreased muscle power in this population [27].…”
Section: ▪▪mentioning
confidence: 99%